Factors Contributing To Socialisation Following Entry Into An Organisation - Tan, Kim Sek (1995)
The time required by a new engineer to become proficient at his or her job is important to both the employee and employer. In this study, data were gathered from 91 engineers who were working in three different manufacturing companies. By correlation analysis and step-wise regression analysis, it was found that Job Characteristics ( Motivating Potential Score), coworker support, supervisory support and role clarity contributed significantly in enabling new engineers to adapt themselves to their work setting and start to contribute to the company